2012
DOI: 10.1103/physrevb.86.075437
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength chiral surface plasmons that carry tuneable orbital angular momentum

Abstract: We show that a helically grooved metal wire supports chiral surface plasmon polaritons (SPPs) that carry nonzero orbital angular momentum (OAM). This OAM can be tuned to have integer or fractional values by adjusting the mode wave vector. The dispersion relation and angular characteristics of the chiral modes are determined numerically and explained with the help of an effective mode index. Chiral SPPs offer the possibility to control both the chirality and the OAM of electromagnetic fields at the subwavelengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Recently, singular optical effects have been discussed in the near field, in particular in relation to chiral surface plasmon (SP) modes which have been shown to carry orbital angular momentum (OAM) [14][15][16][17]. But until now, singular SP modes and associated spin-orbit coupling have only been probed in the near field [18][19][20].…”
Section: Pacs Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, singular optical effects have been discussed in the near field, in particular in relation to chiral surface plasmon (SP) modes which have been shown to carry orbital angular momentum (OAM) [14][15][16][17]. But until now, singular SP modes and associated spin-orbit coupling have only been probed in the near field [18][19][20].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Currently, chiral nanostructures draw promising routes for enhancing singular optical signatures, thus providing extended control over new functionalities in metamaterial science [5] and biomimetics engineering [6,7]. Interestingly, while the connection between optics and chirality is well established for 3 dimensional (3D) chiral structures, the interaction of chiral light with 2D chiral objects is a topic of on-going debate [8][9][10], with strong potential in physical chemistry for chirality enhancement in the near field [11][12][13].Recently, singular optical effects have been discussed in the near field, in particular in relation to chiral surface plasmon (SP) modes which have been shown to carry orbital angular momentum (OAM) [14][15][16][17]. But until now, singular SP modes and associated spin-orbit coupling have only been probed in the near field [18][19][20].…”
mentioning
confidence: 99%
“…Typically, silicon wires with diameters in nano-scale have been introduced to support propagation of light with little loss [18], but much of the electromagnetic energy is actually propagated outside the wire, leading to serious problem of coupling between adjacent wires. Up to now, high efficiency optical applications for OAM propagating in nano-scale are still missing although some chiral surface plasma has been observed [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This offers the possibility to control both the chirality and the orbital angular momentum of electromagnetic fields at the subwavelength scale. Different plasmon chiral nanostructures draw promising routes for enhancing the optical near field, thus providing extended control over new functionalities in metamaterial science, biomimetics engineering and biosensing [6][7][8][9]. New results show unique possibilities for generating far-field optical vortex beams from near-field optical chirality [10].…”
Section: Introductionmentioning
confidence: 99%
“…The phase singularities represent centers of local circulating optical power flows, or simply optical vortices [5]. On the other hand, it has been demonstrated that a helically grooved metal wire supports the propagation of chiral surface plasmon polaritons [6]. This offers the possibility to control both the chirality and the orbital angular momentum of electromagnetic fields at the subwavelength scale.…”
Section: Introductionmentioning
confidence: 99%